CD1lb/CD 18 Mediates the Neutrophil Chemotactic Activity of Fibrin Degradation Product D Domain - Gross, Thomas J; Leavell, Keith J; Peterson, Michael W (Thrombosis and Haemostasis, 1997)
Coagulation and fibrinolysis universally accompany tissue injury and repair. The accumulation of regionally generated fibrin degradation products (FDP) may modify the local inflammatory response. We have found FDP to be potent neutrophil chemotaxins. We separated plasmin FDP by chromatofocusing and found chemotactic activity limited to fractions containing the fibrinogen D domain (D-D dimer and D monomer). The bioactivity of the D-D dimer did not require an intact cross link site as removal of this sequence with puff adder venom or hypocalcemic plasmic digestion did not decrease chemotaxis. Peptide inhibition studies confirmed that the chemotactic region did not involve terminal gamma chain sequences or alpha chain RGD motifs. The internal gamma chain peptide KYGWTVFQKRLDGSV (PI), known to bind CDllb/CD18, exhibited concentration dependent chemotactic activity. Similarly, monoclonal antibodies directed against CD1lb/CD18 blocked PMN migration to FDP without similar inhibition of chemotaxis to IL-8 or LTB4. Thus, neutrophil chemotaxis to FDP is mediated by interactions between the fibrinogen D domain and CD1lb/CD18.